2020
DOI: 10.1111/jcap.12287
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Internet addiction on sleep quality in adolescents

Abstract: Problem This cross‐sectional type study was conducted to investigate the effect of Internet addiction on sleep quality in adolescents. Methods The study was conducted between September and December 2017 in three high schools located in the city center of Erzincan determined according to three socioeconomic levels. The population of the study was composed of 9th, 10th, 11th, and 12th grade students in the high schools determined. In the study, sample group selection was not made and all students, for whom paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…For example, in the study by Canan et al in 16-year-old Internet-addicted adolescents, along with a decrease in the time of nighttime sleep, frequent night awakenings were also recorded [ 61 ]. A recent study of Turkish adolescents also showed a decrease in the duration of nighttime sleep, an increase in sleep onset latency, and dyssomnia, recorded by an increase in the mean score of the PSQI in adolescents with IA [ 41 ]. Similar associations using the PSQI have also recently been described for Indian adolescents [ 62 ], Turkish and Bangladeshi students [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the study by Canan et al in 16-year-old Internet-addicted adolescents, along with a decrease in the time of nighttime sleep, frequent night awakenings were also recorded [ 61 ]. A recent study of Turkish adolescents also showed a decrease in the duration of nighttime sleep, an increase in sleep onset latency, and dyssomnia, recorded by an increase in the mean score of the PSQI in adolescents with IA [ 41 ]. Similar associations using the PSQI have also recently been described for Indian adolescents [ 62 ], Turkish and Bangladeshi students [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kawabe et al recorded that going to sleep later and awakening later, a decrease in total sleep duration, and an increased general index of sleep problems according to the Child and Adolescent Sleep Checklist in adolescents with IA [ 27 ]. A large number of studies show a significant decrease in the quality of nighttime sleep, verified using the Pittsburgh Sleep Quality Index (PSQI) questionnaire [ 37 , 38 , 39 , 40 , 41 ]. Besides, daytime sleepiness was increased in adolescents with IA [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each research assistant was then sent an advertisement containing the introduction to the survey and a link to the on-line survey, produced by the Wenjuanxing platform, to connect with the WeChat group or QQ group of their classes or their friends' classes. Consequently, it was not possible to calculate the number of potential respondents and completion rates (Callegaro & DiSogra, 2008). The purpose of the survey was explained and students were informed that their participation was completely voluntary and that any information they provided would be anonymous in order to protect their privacy rights.…”
Section: Participations and Proceduresmentioning
confidence: 99%
“…Kawabe et al recorded the fact of going to sleep later and awakening later, a decrease in total sleep duration, and an increased general index of sleep problems according to the Child and Adolescent Sleep Checklist in adolescents with IA [7]. A large number of studies show a significant decrease in the quality of night sleep, verified using the Pittsburgh Sleep Quality Index (PSQI) questionnaire [17][18][19][20][21]. Besides, daytime sleepiness was increased in adolescents with IA [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%